Exigências nutricionais para mantença e lactação e perfil metabólico de vacas F1 Holandês x Gir e Gir, em diferentes planos nutricionais - Paolo Antonio Dutra Vivenza (2016)
Twelve lactating cows were used, six of the Gir genetic group (initial mean live weight of 441 kg) and six of the crossbreeding of Holstein x Gir (initial mean live weight of 535.5 kg), with the objective of determining the nutritional requirements for maintenance and lactation, as well to evaluate the metabolic profile of these genetic groups in different nutritional plans. The first chapter deals with the concept and use of energy by the animal organism, as well as the study of the metabolic profile and the lactation curve in Bos taurus indicus animals and their crosses. In the second chapter, the data on intake, apparent digestibility of nutrients and nitrogen balance of F1 Holstein x Gir and Gir cows are presented during the determination of the nutritional requirements of maintenance and lactation. Twelve lactating cows were used, six of each genetic group, kept in individual stalls receiving corn silage and concentrate, as recommended by the NRC (2001). The animals were evaluated from the 1st to the 15th week in lactation. The equations proposed by the NRC (2001) were used to estimate the energy density of the diets. Crossbreed cows (Holstein x Gir) showed higher dry matter intake (DMI) and other nutrients in all periods, compared to Gir. These group presented DMI stability over the evaluated periods, with a mean value of 11.22 kg DM/ day. Crossbreed cows presented lower DMI in the period 1 (16.00 kg DM / day, 3.10% live weight), in relation to the others (17.42 kg DM / day, 3.33% live weight), reflecting the differences obtained in milk production between the periods. The two genetic groups showed no differences in nutrient digestibility, nor were differences in digestibility observed between levels of consumption. The prediction equation of the digestible energy (ED) from the total digestible nutrient values (NDT) presented low prediction capacity, whereas the prediction equations of the metabolizable energy (ME) from the ED and prediction of the net energy (NE) from the NDT presented higher prediction capacity. Cows of both genotypes presented equal loss of fecal and urinary nitrogen, in relation to the total nitrogen ingested. Crossbreed cows (Holstein x Gir) presented greater efficiency of conversion of nitrogen to milk, in relation to the Gir. The different genotypes presented equal efficiency in total retention of nitrogen in products. In the third chapter, energy partitioning data and the nutritional requirements of net energy of maintenance (NEm) and lactation (NEl), as well as the efficiency of use of metabolizable energy, are presented in crossbreed Holstein x Gir and Gir cows in the initial third of lactation. Twelve empty lactating cows were used, six of each genetic group, kept in individual stalls receiving corn silage and concentrate, as recommended by NRC (2001). Three digestibility tests were carried out, followed by measurement of the heat production (HP) in a respirometric chamber. Crossbreed cows had higher intake of crude, digestible, metabolizable and net energy in all the evaluated periods, in relation to the Gir, reflecting the higher intake of dry matter (DMI). Cows of both genetic groups had similar losses of crude energy in the form of feces (28.17%) and methane (6.37%). The metabolizability (q) of the diet had no differences between periods and genetic groups, with a mean value of 0.59. Crossbreed cows had higher net energy secreted in milk, compared to Gir. The net energy requirement for the production of 1 kg milk was 0.77 Mcal / kg of milk, which corresponds to 0.2393 kg total digestible nutrients (NDT) / kg of milk, similar between the groups. F1 cows presented higher milk production and total solids. Gir cows had significant weight gain and body condition score. Crossbreed cows were more productive and efficient, in relation to the percentage of energy secreted in milk, as well as in relation to the emission of greenhouse gases (GHG) per product generated (milk and total solids). Gir cows have lower requirement for metabolizable energy (115.88 kcal / kg 0.75) and net (79.39 kcal / kg 0.75) maintenance, in relation to crossbreed cows (123,14 and 88, 12 kcal / kg 0.75). Both genetic groups require lower metabolizable energy of maintenance (EMm) compared to that suggested by the major committees and international tables of nutritional requirements. The efficiency of use of metabolizable energy for maintenance and lactation was 0.70, similar between groups. Crossbreed cows directed most of the net energy to milk production, compared to Gir cows, which directed most of the maintenance functions. In the fourth chapter we present the data regarding the metabolic profile, performance and feed efficiency of crossbreed Holstein x Gir and Gir cows from calving at the 105th day in lactation. Twelve lactating cows were used, six of each genetic group. The dry matter intake (DMI), milk production and composition, body condition score (ECC) and live weight were evaluated weekly, from the 1st to the 15th week. Non-esterified fatty acids (NEFA), creatinine, total protein, albumin, globulins, triglycerides, cholesterol and aspartate aminotransferase (AST) were evaluated for metabolic profile study. The experimental design was completely randomized, with a scheme in subdivided plots. Analyzes of variance were performed using the GLM procedure of the statistical package SAS. Crossbreed cows presented higher DMI (16.96 kg / day), corrected milk production (19.20 kg / day), feed efficiency (1.13 kg milk / kg DM), NEFA and AST concentration, as well as higher variation In the ECC, evidencing moderate mobilization of body reserves. The uptake phase of lactation was observed in crossbreed cows, unlike in Gir cows. These, in turn, presented greater weight gain and ECC with the course of lactation, and DMI (11.22 kg / day) remained constant during the period evaluated. Crossbreed cows were more productive and efficient for milk production, being able to use body reserves at the beginning of lactation. Cows from the Gir group had greater aptitude for weight gain and body condition during lactation, in detriment to milk production. In the fifth chapter, the consumption, apparent digestibility of nutrients, energy partition, metabolic profile and the bioeconomic efficiency of crossbreed Holstein x Gir and Gir cows submitted to different nutritional plans were evaluated. Twelve lactating cows were used, empty, six of each genetic group. During the first 105 days in lactation (AD) the animals were given ad libitum feed. In 106 ° DEL, a 15% DMI restriction was imposed, followed by a further 30% DMI restriction, each lasting 20 days. A digestibility test was performed, followed by the measurement of heat production (CP) in each nutritional plan. The metabolic profile of the animals in the different plans was evaluated. The experimental design was completely randomized, with a scheme in subdivided plots. Nutritional restrictions did not cause changes in nutrient digestibility, being similar among genetic groups. DMI and energy decreased with increased nutritional restrictions in both groups, being higher for crossbreed cows in all nutritional plans, reflecting the higher production of milk and solids. These cows emitted less methane in relation to milk and solids production in the nutritional restriction of 15%, in relation to the ad libitum period. The 15% restriction did not alter milk production, live weight and body condition in both groups. Gir cows had greater body condition in all nutritional plans. Crossbreed cows had greater mobilization of body reserves in the nutritional restriction of 30%, evidenced by the increase of NEFA concentrations. The nutritional restriction did not alter the metabolic profile of Gir cows. Better utilization of nitrogen was observed for crossbreed cows with nutritional restriction. These cows had better bioeconomic efficiency in nutritional restriction of 15%, and could be used as a strategy to reduce food costs.